ChemInform Abstract: 2‐Pyridone Synthesis Using 2‐(Phenylsulfinyl)acetamide. Issue 21 (2nd May 2013) - Fujii, Masaya; Nishimura, Takuya; Koshiba, Takahiro; Yokoshima, Satoshi; Fukuyama, Tohru
Abstract Title compounds are prepared by the present new and efficient protocol including the 1, 4‐addition of 2‐(phenylsulfinyl)acetamide to α, β‐unsaturated ketones followed by cyclization and sulfoxide elimination.